Association between estrogen levels and temporomandibular disorders: a systematic literature review - Berger, Marcin; Szalewski, Leszek; Bakalczuk, Magdalena; Bakalczuk, Grzegorz; Bakalczuk, Szymon; Szkutnik, Jacek (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: To evaluate whether the hypothesis that estrogen levels are associated with temporomandibular disorders (TMD) in humans can be confirmed or contradicted by available literature. Material and methods : A systematic review based on the content of PubMed, Scopus, and Cochrane Library databases was performed. Studies were identified using a combination of key words ‘temporomandibular disorder’ and ‘estrogen’. Nine studies were included into our review. Results: The relationship between estrogen levels and TMD was found in seven out of nine reviewed papers. Results from two papers suggest that a high estrogen level is associated with an increased prevalence of TMD. Five additional papers found a relationship between a low estrogen level and an increase in TMD pain. In considering the value of evidence and inconsistencies of results in the reviewed publications, we state that there is weak evidence to support the hypothesis that estrogen levels are associated with TMD. Conclusions : Results of reviewed studies were divergent and sometimes contradictory. One possible explanation is that estrogen influences TMD pain processing differently than temporomandibular joints (TMJ) structures, as shown in many animal studies. Estrogen may influence TMD pain processing differently than TMJ structures. We suggest consideration of the dual action of estrogen when planning future studies on its association with TMD.